2017
DOI: 10.1101/140293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

mTORC2/AKT/HSF1/HuR constitute a feed-forward loop regulating Rictor expression and tumor growth in glioblastoma

Abstract: Running title: Feed-forward loop signaling regulates mTORC2 Word count (text) = 4483 Word count (abstract) = 227 Figure count = 7 Table count = 1 Reference count = 49 2 ABSTRACT Overexpression of Rictor has been demonstrated to result in increased mTORC2 nucleation and activity leading to tumor growth and increased invasive characteristics in glioblastoma multiforme (GBM). However the mechanisms regulating Rictor expression in these tumors is not clearly understood. In this report, we demonstrate that Rictor i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…FAM3C, family with sequence similarity three member C; YY1, Ying-Yang 1; HSF1, heat shock factor 1; TGFβ, transforming growth factor beta; Akt, protein kinase B role in activating Akt, it has also been reported that Akt activation also activates YY1 and HSF1 expressions. 47,48 TGFβ activated FAM3C-YY1-HSF1 axis to promote proliferation and migration in various breast cancer cell lines. Collectively, these findings together suggested that FAM3C likely initiates the crosstalks among YY1, HSF1 and Akt, finally causing excessive Akt activation to trigger tumour growth and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…FAM3C, family with sequence similarity three member C; YY1, Ying-Yang 1; HSF1, heat shock factor 1; TGFβ, transforming growth factor beta; Akt, protein kinase B role in activating Akt, it has also been reported that Akt activation also activates YY1 and HSF1 expressions. 47,48 TGFβ activated FAM3C-YY1-HSF1 axis to promote proliferation and migration in various breast cancer cell lines. Collectively, these findings together suggested that FAM3C likely initiates the crosstalks among YY1, HSF1 and Akt, finally causing excessive Akt activation to trigger tumour growth and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that HuR promotes proliferation in cancer cells (20,38), including wild-type gliomas (39,40). Here, we investigated the effect of HuR expression on cell proliferation in cancer cells that harbor a natural heterozygous IDH1 mutation.…”
Section: Hur Promotes Cell Proliferation and Invasion In Mutidh1 Canmentioning
confidence: 98%
“…HuR has been studied as an important driver and facilitator of cancer for almost 20 years and has been identified to be a critical target in numerous models of cancer. HuR has been found to regulate and contribute to almost every hallmark of cancer (Hanahan & Weinberg, ): (a) sustaining proliferative signaling (Holmes et al, ; W. Wang, Caldwell, Lin, Furneaux, & Gorospe, ; Yuan, Sanders, Ye, Wang, & Jiang, ; Z. Zhang, Huang, Zhang, & Zhou, ); (b) evading suppression of growth (Balkhi et al, ; Ghosh et al, ); (c) promoting invasion and metastasis (Z. Li, Wang, Hu, Xu, & Xu, ); (d) enabling replicative immortality (Tang et al, ); (e) inducing angiogenesis (Goldberg‐Cohen, Furneauxb, & Levy, ; Levy et al, ; Osera et al, ); (f) resisting cell death (Blanco, Jimbo, et al, ; Guo et al, ; G. L. Lin et al, ; H. Zhu et al, ), (g) deregulating cellular energetics (Cascajo et al, ; Diaz‐Munoz et al, ; Zarei et al, ) (h) promoting tumor‐associated inflammation (W. Peng et al, ; S. Sun et al, ), and (i) avoiding immune destruction (Brauss et al, ). Further underscoring the importance of HuR as a target in cancer, increased levels of HuR have been associated with tumor aggressiveness and poor outcomes in numerous tumor types (Miyata et al, ).…”
Section: Hur As Critical Mediator Of Cancer Progressionmentioning
confidence: 99%